(untitled) (Contemporary Journal of Social Science Review, 2026)
In the present day, South Asian politics has seen a shift towards virtualization of political contestation, with algorithmic social media platforms emerging as the major terrain for the construction, contestation and subversion of democratic legitimacy. Drawing on the theory of cultural hegemony, Antonio Gramsci; the concept of public sphere, Jürgen Habermas; and subaltern counter-publics, Nancy Fraser, the study is qualitative and uses Norman Fairclough’s Three-Dimensional Framework for Critical Discourse Analysis (CDA) to explore digital narratives from three high-stakes geopolitical crises: the Indian Farmers’ Protests (2020-2024), Pakistan’s Regime Change (2022), and the Bangladesh July Revolution (2024) to see how state apparatuses use digital architectures to impose hegemony by paternalistic othering, legal-rational framing, and computational propaganda. At the same time, the study explores the ways that the marginalized civic networks are able to invert these state-sponsored discourses by returning derogatory terms to their own usage, the deployment of somatic imagery, and through transnational connective action. The results show an extremely ambivalent situation, in which the digital public sphere in South Asia is being subjected to a process of ‘digital re-feudalization’ by the state, even as digital political hegemonies are always fragile and susceptible to the resilient and decentralized contestation of digital counter-publics.